Glass-fiber membranes for storing, transportation and further characterization of agricultural plant biomaterial. Issue 1 (January 2020) - Vasyukova, I; Zakharova, O; Altabaeva, Yu; Kondakov, S; Snegin, E; Romanova, T; Gusev, A
Abstract: The modified glass-fiber membranes possess high mechanical strength, good wetting and storage capacity, these properties render them a promising medium for storing dry biomaterial collected from agricultural plants. We have studied the applicability of this method for storing biomaterial collected from cucumber, tomato and potato in the form of dried spots on glass-fiber matrices for further ecological and phytosanitary studies. Also preservation of Phytophthora infestans deoxyribonucleic acid in the potato tuber and tomato fruit biomaterial stored on glass-fiber membranes has been evaluated. It has been revealed via real time polymerase chain reaction assays that in dried spots on glass-fiber membranes more than 90% of the plant deoxyribonucleic acid is preserved after seven-day storage. The method of electrophoretic isolation has shown that the condition of Phytophthora infestans deoxyribonucleic acid in the plant biomaterial stored on glass-fiber membranes is similar to the control after any storage period. In all the studied cases the storage conditions of the dried spots on glass-fiber matrices had no influence on the target deoxyribonucleic acid preservation. The obtained results prove usability of membrane carriers for crop science as a whole and detection of plant diseases in particular, and for food quality monitoring, especially carried out in the field.